2017
DOI: 10.1071/aj16184
|View full text |Cite
|
Sign up to set email alerts
|

Determination of T2 cut-off for shale reservoirs: a case study from the Carynginia formation, Perth Basin, Western Australia

Abstract: Over recent decades, the low-field Nuclear Magnetic Resonance (NMR) method has been consistently used in the petroleum industry for the petrophysical characterisation of conventional reservoirs. Through this non-invasive technique, the porosity, pore size distribution and fluid properties can be determined from the signal emitted by fluids present in the porous media. Transverse relaxation (T2) data, in particular, are one of the most valuable sources of information in an NMR measurement, as the resulting sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Testamanti and Rezaee 9 found that conventional centrifuge speed would not be enough to remove the water from the tiny pores, which could lead to inaccurate T 2 data for estimating the CBW in shale samples. Increasing the centrifuge speed could extract the water in the small pores.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testamanti and Rezaee 9 found that conventional centrifuge speed would not be enough to remove the water from the tiny pores, which could lead to inaccurate T 2 data for estimating the CBW in shale samples. Increasing the centrifuge speed could extract the water in the small pores.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Increasing the centrifuge speed could extract the water in the small pores. 9 However, Yuan et al 10 found that under 4500 rpm, a maximum capillary pressure of 315 psi will be created, which might eventually damage the samples. Furthermore, the thermal treatment provided by Testamanti and Rezaee 9 could be an alternate way for more accurate CBW estimation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation